2012
DOI: 10.1152/ajpregu.00577.2011
|View full text |Cite
|
Sign up to set email alerts
|

Permeability properties of the teleost gill epithelium under ion-poor conditions

Abstract: Permeability properties of the goldfish gill epithelium were examined in vivo and in vitro following exposure to ion-poor water (IPW) conditions. In gill tissue of IPW-acclimated goldfish, transcript abundance of tight junction (TJ) proteins occludin, claudin-b, -d, -e, -h, -7, and -8d increased, whereas ZO-1 and claudin 12 mRNA decreased and claudin-c was unaltered. In association with these changes, TJ depth increased among gill pavement cells (PVCs) and gill PVCs and mitochondria-rich cells (MRCs). PVC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…Several lines of evidence support a barrier-forming role for ZO-1, occludin, claudin-b, -c and -3 in fish [77,78], whereas claudin-12 and -15 in rats seem to possess pore-forming characteristics [79,80]. Moreover, the up-regulation of ZO-1 and occludin [81] and down-regulation of claudin-15 [82] attenuated the loss of the Fig.…”
Section: Trp Improved the Intestinal Barrier Function And Antioxidantmentioning
confidence: 97%
“…Several lines of evidence support a barrier-forming role for ZO-1, occludin, claudin-b, -c and -3 in fish [77,78], whereas claudin-12 and -15 in rats seem to possess pore-forming characteristics [79,80]. Moreover, the up-regulation of ZO-1 and occludin [81] and down-regulation of claudin-15 [82] attenuated the loss of the Fig.…”
Section: Trp Improved the Intestinal Barrier Function And Antioxidantmentioning
confidence: 97%
“…Moreover, ZO-1, occludin, claudin-b, claudin-c, claudin-3 are the barrier-forming TJ proteins in fish [26], whereas claudin-12 and claudin-15 in rats seem to possess pore-forming characteristics [13]. In this study, dietary choline supplementation significantly up-regulated the ZO-1, occludin, claudin-b, claudin-c, claudin-3 mRNA levels in the gills of grass carp, implying that choline might improve the barrier function of fish gill.…”
Section: Choline Regulated Tj Proteins and Mlck Mrna Levels In The Gimentioning
confidence: 99%
“…A growing number of researches indicated that the gill epithelium barrier is partly regulated by tight junctions (TJ) [25]. Moreover, in fish gill, TJ complex was composed by transmembrane (such as Occludin and Claudins) and cytoplasmic (ZO-1) TJ proteins [26]. It was reported that changes in the expression of gill TJ proteins could contribute to the major permeability variation in Southern Flounder [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown select TJ proteins of the gill epithelium to be sensitive to environmental change as well as endocrine factors that mediate the systemic response of fishes to varying environmental conditions (for a review see Chasiotis et al, 2012a). These TJ proteins include a number of claudin as well as transmembrane TJ proteins such as occludin (Ocln) and Tric (Chasiotis et al, 2012b;. In addition, cortical proteins such as zonula occludens 1 (ZO-1) have been reported to alter in response to environmental or systemic change (Chasiotis et al, 2012b).…”
Section: Research Articlementioning
confidence: 99%
“…These TJ proteins include a number of claudin as well as transmembrane TJ proteins such as occludin (Ocln) and Tric (Chasiotis et al, 2012b;. In addition, cortical proteins such as zonula occludens 1 (ZO-1) have been reported to alter in response to environmental or systemic change (Chasiotis et al, 2012b). However, despite an increasing number of studies examining gill epithelium TJ proteins in relation to changes in the external environment, the contribution of gill epithelium TJ proteins to the establishment and maintenance of paracellular permeability properties in this tissue remains poorly understood.…”
Section: Research Articlementioning
confidence: 99%